Novel studies on erbium-doped fiber amplifier - John Atuh, J. (University Malaysia Sarawak, UNIMAS., 2000)
This project focus on application of EDFA in fiber communication network, determination of the amplifications concept and system design technology applied in EDFA and to compare the performance of EDFA over other optical amplifiers.